Thouhgts on Music Ethnography in Urban Indonesia: From Yogyakarta Recordings to Translocal Popular Culture in the Melayu Borderlands - Max Richter (Antropologi Indonesia, 2011)
Previous studies on Indonesian music focused on cultural heritage and traditional preservation or western-style modern music such as pop and rock music. Both were perceived as separate genre, even modern music often downplayed traditional one. The author argues analysis of hybrid genre like keroncong and dangdut would provide more complicated picture than such dichotomy. He explained long history of cultural exchanges in various parts of Indonesia which showed these two genres influenced each other. As a case study the author presents urban music as main character of urban social lives in Indonesia. This article depicts street music and campursari in Yogyakarta and linking it to popular cultures in some cities. Popular culture refers to informal recreation in different social settings. Eventually, this article reveals new ways to understand relation between music style and social identity in urban Indonesia. Key words: intercultural exchange, popular culture, translocal, music style, identity